IMPROVING STUDENTS’ WRITING RECOUNT TEXT ACHIEVEMENT THROUGH MIND MAPPING TECHNIQUE IN JUNIOR HIGH SCHOOL - Maria Rosa Marpaung; Johan Sinulingga (Universitas Negeri Medan, 2012)
This study concerns with improvement of students’ achievement in writing recount text through mind mapping technique in Junior High School. The subject of the study was the students in SMP Free Methodist 1 Medan, class VIII-1 which consisted of 37 students. This study was conducted by applying Classroom Action Research. The procedure of this research was done in two cycles in six meeting. The mean of students’ score in test I was 67.24. It was increased in test II to 72.78 and in test III, it became 78.79. The improvement was not only showed in the mean of the students’ score but also in the number of students who got point up to 75. In test I, the number of students who got point up to 75 was only 5.4%. In test II, the number was increased to 29.8% while in test III it became 81.1%. Based on the diary notes, observation sheet and questionnaire sheet, it was found that the students gave good responds in the teaching and learning process. Based on the result of quantitative and qualitative data, it can be concluded that the application of mind mapping technique had improved the junior high school students’ achievement in writing recount text. Keywords: Writing, Recount Text, Mind Mapping, Junior High School